MENINGKATKAN HASIL BELAJAR MATEMATIKA DENGAN PENDEKATAN STEAM DI SEKOLAH DASAR - Kartikasari; Herlina Usman; Resi Ratna Suminar; Nuryani (Jurnal Pendidikan dan Kebudayaan (JURDIKBUD), 2022)
This study aims to improve the learning outcomes of mathematics students in grades VI (SDN Kampungsawah 01, District Rumpin) with this type of action research. The subjects in this study were sixth grade students at SDN Kampungsawah 01 for the academic year 2022–2023, with a total of 28 students, consisting of 10 male students and 18 female students. Data obtained through tests, observations, and documentation Data analysis techniques using qualitative descriptive analysis According to the data analysis results, there was an increase in learning management by teachers, learning activities, and student learning outcomes from cycles I, II, and III, with each cycle obtaining the value of aspects of learning management by teachers in the observation phase at intervals of 2.12 with a predicate of "good enough," then increasing to 2.76 with a predicate of "good," 3.14 with a predicate of "good," and 3.5 with a predicate of "very good."At the observation stage, it was predicted that things would go well by 25%, and in cycle I it increased to 46.42% predicted good, then in cycles II and III it increased to 35.71% and 64.28% predicted very well.Learning outcomes have improved, particularly at the observation stage, where 21.41% are completed, cycle I is 53.57%, cycle II is 71.43%, and cycle III is 100%.Thus, it can be concluded that the application of the STEAM approach (Science, Technology, Engineering, Arts, and Mathematics), assisted by the Geogebra application, can improve the results of the mathematics learning of fifth grade students in SDN Kampungsawah 01, Rumpin District.